Wages and Industrial Clusters in Rio Grande Do Sul (Brazil) - Leonardo Monasterio; Mauro Salvo (European Regional Science Association (ERSA), 2006)
The paper estimates the effects of agglomeration economies on wages of industrial workers in the state of Rio Grande do Sul, Brazil. The techniques of Exploratory Analysis of Spatial Data are used to locate the clusters of the states' industry in 2000. Then, this information was combined to census microdata in order to run wage regressions inspired by the empirical tests of New Economic Geography models (HANSON, 1998, specially). The results were statistically and economically significant: even when controlled by demographic variables, the individual wages of industrial workers were higher on the cities with larger population, more urbanized, higher market potential and closer to the economic centre of the Rio Grande do Sul. These findings indicate how intense the economic forces that shape the spatial structure of the state are, and suggest changes in current regional policies.
Keywords: 330